2017
DOI: 10.1111/1750-3841.13627
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Proteolysis with Alkaline Protease Following High Hydrostatic Pressure Treatment on IgE Binding of Buckwheat Protein

Abstract: Buckwheat is a popular food material in many Asian countries and it contains major allergenic proteins. This study was performed to analyze the effects of hydrolysis with alkaline protease following high hydrostatic pressure (HHP) treatment on the IgE binding of buckwheat protein. Extracted buckwheat protein was treated with HHP at 600 MPa for 30 min and hydrolyzed with alkaline protease for 240 min. IgE binding was examined using an enzyme-linked immunosorbent assay (ELISA) with serum samples from 14 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In the case of amyloglucosidase, the highest protein content of 42.10 g/100 g was obtained at 1.50 U g −1 amyloglucosidase with a rather high polyphenol content of 9.33 g/100 g. These results can be attributed to biocatalyst agglomeration and diffusional problems of substrates at higher enzyme loads, for example 7.50 U g −1 . Similar findings – that excess enzyme present in the reaction decreased the efficiency per mass unit of biocatalyst in other enzyme reactions – have also been reported …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the case of amyloglucosidase, the highest protein content of 42.10 g/100 g was obtained at 1.50 U g −1 amyloglucosidase with a rather high polyphenol content of 9.33 g/100 g. These results can be attributed to biocatalyst agglomeration and diffusional problems of substrates at higher enzyme loads, for example 7.50 U g −1 . Similar findings – that excess enzyme present in the reaction decreased the efficiency per mass unit of biocatalyst in other enzyme reactions – have also been reported …”
Section: Resultsmentioning
confidence: 98%
“…Similar findings -that excess enzyme present in the reaction decreased the efficiency per mass unit of biocatalyst in other enzyme reactions -have also been reported. 20,22 This also suggested that the enzyme treatment of both -amylase and amyloglucosidase was the key procedure to recover polyphenol in the buckwheat protein products. Indeed, a synergistic action of dual-enzyme treatment of 1.08 U mg −1 -amylase and 1.50 U g −1 amyloglucosidase was clearly observed from the production of polyphenol-enriched buckwheat protein (E-BWP), with a higher content of both protein (49.07 g/100 g) and polyphenol (11.35 g/100 g), as shown in Table 2.…”
Section: Preparation and Characterization Of High-polyphenol Buckwheamentioning
confidence: 99%
“…Although BPIs have excellent nutritional properties, there are many reports of immunoglobulin (Ig)E‐mediated allergies, which are associated with severe anaphylaxis. To reduce this negative attribute of BPIs, Lee et al 76 . treated these proteins with HP at 600 MPa for 30 min and then hydrolyzed them with alkaline protease for 240 min.…”
Section: Modifications Of Pseudocereal Proteinsmentioning
confidence: 99%
“…75 Although BPIs have excellent nutritional properties, there are many reports of immunoglobulin (Ig)E-mediated allergies, which are associated with severe anaphylaxis. To reduce this negative attribute of BPIs, Lee et al 76 treated these proteins with HP at 600 MPa for 30 min and then hydrolyzed them with alkaline protease for 240 min. The results clearly showed that the method of hydrolysis with alkaline protease after treatment with HP could be applied to reduce the binding of IgE to BPI by up to 100%.…”
Section: High Hydrostatic Pressurementioning
confidence: 99%